Efektivitas Program Pesantren dalam Merehabilitasi Pecandu Narkoba di Pondok Pesantren Bahrul Maghfiroh Lowokwaru Kota Malang - Wardoyo, Eko Hadi; Muhtadi, Muhtadi; Muslim, Muhamad Agus (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
ABSTRACT Drug abuse is a serious issue that damages the physical, mental, and social condition of its users. Rehabilitation efforts are crucial in helping addicts return to normal life. This study raises the theme of the effectiveness of pesantren-based rehabilitation programs, focusing on Bahrul Maghfiroh Islamic Boarding School in Lowokwaru, Malang City, which serves as a Compulsory Reporting Institution (IPWL) in a faith-based social rehabilitation program. This research uses a qualitative approach with descriptive methods. The research location is Bahrul Maghfiroh Islamic Boarding School. Data collection techniques include in-depth interviews with the pesantren caregivers, rehabilitation mentors, and students undergoing the program, as well as direct observation and documentation of daily activities. Data were analyzed through the process of data reduction, data presentation, and conclusion drawing. The findings show that the rehabilitation program at the pesantren proved effective. The program includes community-based therapy, spiritual therapy through worship and religious study, herbal therapy as an alternative treatment, and outpatient programs. A religious environment, a familial approach, and consistent guidance are the main factors contributing to the program’s success. The addicts experienced positive behavioral changes, increased spiritual awareness, and readiness to reintegrate into society. Keywords : Effectiveness, Rehabilitation, Drugs, Pesantren, Bahrul Maghfiroh